The effectiveness of physical exercise with structured light on students' sleep quality - Zulkifli Keya Husain; Giofandi Samin; Gilang Ramadan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to evaluate the effectiveness of a structured light jogging program in improving sleep quality among students, as measured by the Pittsburgh Sleep Quality Index (PSQI). A qualitative approach with a pre-experimental one-group pretest-posttest design was employed. A total of 30 students with PSQI scores >5 were selected purposively. The intervention consisted of 16 jogging sessions over eight weeks at light to moderate intensity. Sleep quality was measured using the PSQI before and after the intervention, and data were analyzed using paired sample t-tests. The results showed a significant reduction in PSQI scores from a mean of 11.29 to 6.35 (p < 0.001). The proportion of students with poor sleep decreased from 83.3% to 26.7%, while those with sufficient and good sleep quality increased accordingly. The structured light jogging program effectively improved sleep quality among university students. This study contributes to the development of non-pharmacological, practical, and low-cost interventions for student health. Further research should explore other exercise types and consider lifestyle and psychological variables.